A Clinical Study On Role Of Gramya Ahara (Dietetics & Life Style) In Aetiopathogenesis Of Prameha (Type 2 Diabetes Mellitus) And Evaluation Of Hypoglycaemic Effect Of Bhudhatryadi Yoga - Bhadoria, Anil; Gupta, Sakshi (International Research Journal of Ayurveda & Yoga, 2021)
Diabetes Mellitus is largely covered under the broad heading of Prameha. However, Apathyanimittaja Prameha (Sushruta), Sthula Pramehi (Charaka) and Avaranjanya Madhumeha described in Ayurvedic literature have similarity with Type-2 Non-Insulin Dependent Diabetes Mellitus (NIDDM). Type 2 diabetes prevalence is rising at alarming rates worldwide because of increased urbanization, high prevalence of obesity, sedentary lifestyles and stress, among other factors. Up to 80% of type 2 Diabetes is preventable by adopting a healthy diet and increasing physical activity. The summary published by “World Diabetes Congress” on 14th Nov.; 2009 “World Diabetes Day” represents that Diabetes affects 246 million people worldwide and is expected to affect some 380 million by 2025. In an effort to find out effective remedy BHUDHATRYADI YOGA was selected for this study. This drug is indicated for the treatment of Prameha in ayurvedic classics. Study was carried out in single group consisting of 30 patients. Results of the treatment were assessed over the period of 45 days. Patients were provided a proper diet chart planned according to the classics, keeping Glycaemic Index of the dietary substances & Calorie requirement of the patients. 6.66% patients obtained control over diseased condition 16.66% patients provided Marked Improvement, Moderate Improvement was observed in 40% of cases, 36.66% cases showed Mild Improvement in Signs and Symptoms.